Cardiovascular Disorders in Adolescents with Chest Pain - Sri Endah Rahayuningsih; Rahmat Budi; Herry Garna (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To detect cardiovascular abnormalities in adolescents with chest pain. Methods: In this cross sectional study, the subjects were 25 adolescents with chest pain who came to the Cardiac Center of Dr. Hasan Sadikin General Hospital, Bandung during the period of January 2008 to January 2011. The presence of established cardiovascular disorders were based on history, physical examination, electrocardiography and echocardiography Results: It was found that 13/25 adolescents with chest pain had cardiovascular abnormalities. Of the 25 teens that came with chest pain, most of which showed normal electrocardiographic results, only 9/25 of those with dysrhythmias experienced sinus tachycardia and 8 had a first degree AV block. Echocardiography examination showed only four patients with abnormal cardiac anatomy. No correlation between nutritional status and chest pain, and cardiovascular abnormalities and chest pain (p = 0.206 and p = 0.632, respectively). There was a positive correlation between sex and cardiovascular abnormalities in adolescents with chest pain (p = 0.007).Chest pain is a prevalent problem that is usually benign and that it frequently signals underlying cardiac disease.Conclusions: Cardiovascular abnormalities in adolescents with symptoms of chest pain are found in some cases. There is no correlation between female and male adolescents with chest pain and cardiovascular abnormalities.Keywords: Adolescents, cardiovascular, chest painDOI: 10.15850/ijihs.v2n1.287